Facile synthesis of tube-shaped Mn-Ni-Ti solid solution and preferable Langmuir-Hinshelwood mechanism for selective catalytic reduction of NOxby NH3 - Liu, J.; Li, X.; Li, R.; Zhao, Q.; Ke, J.; Xiao, H.; Wang, L.; Liu, Shaomin; Tade, Moses; Wang, Shaobin (2018)
© 2017 We present a tube-shaped Mn-Ni-Ti solid solution for the selective catalytic reduction of NO x with NH 3 (NH 3 -SCR) through a facile self-templated urea-homogeneous precipitation method, which leads to the fine dispersion of the MnO x and NiO x active species in the TiO 2 lattice. The ratio of Mn/Ni/Ti is an important factor to affect the crystallinity of Mn-Ni-Ti solid sulotion, and the catalyst with a Mn/Ni/Ti ratio of 2/3/5 (Mn2-Ni3) exhibits the significant structure distortion. The abundant surface defects induce more generation of Mn 4+ species, surface adsorbed oxygen and Lewis acid sites, and acclerate the adsorption and activation of NO molecules. The appropriate Mn/Ni ratio inhibits the competitive adsorption of NH 3 with NO, and facilitates the Langmuir-Hinshelwood (L-H) mechanism to form N 2 , which acts as a much more rapid pathway in comparison to the parallel one following Eley-Rideal (E-R) mechanism. The readily occurence of L-H mechanism significantly improves the SCR performance of catalyst.